Influence of Social Media to Encourage Community Participation in Indonesia Government Administration - Pate, Nasir; Sam, Muliani; Nilwana, Andi; Nonci, Nurjannah (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2025)
This study aims to analyze the influence of social media use, particularly WhatsApp, on community participation in the government administration process in Kulo Sub-district, Sidenreng Rappang Regency, Indonesia. Complex Central Symptoms model was used to understand the central factors that encourage citizen participation. Data was collected through in-depth interviews, participatory observation, and document analysis using a descriptive qualitative approach. The results showed that WhatsApp improved communication efficiency between the community and the government, accelerated the service process, and increased transparency and accountability. Most respondents rated the use of WhatsApp as easy and the response of officers as fast. However, the study also identified key constraints, such as low digital literacy and limited technological infrastructure in rural areas. The implications of this study include the need to strengthen digital literacy through training programs for communities and government officials and the development of more inclusive technological infrastructure. This research makes a theoretical contribution to the e-government literature and offers practical solutions for technology-based public service innovation in rural areas.